Analisis Model Pembelajaran Bilingual Yang Efektif Untuk Siswa Sekolah Dasar - Nadila, Elvira Resti Audin; Miftakhurrozzaq, Muh; Pramudita, Sevia Ashri Tri; Nirmalasari, Nisrina Nadia; Arifani, Selda; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background: This research discusses the various learning models used in bilingual classes in primary schools. This research aims to analyse various effective bilingual learning models for primary school students, so as to contribute to the development of learning methods that can improve students' language skills, confidence, and learning quality. This research uses the literature review research method which is needed to explore topics and issues related to the research to be investigated. Some of the approaches reviewed include cooperative models such as Inside-Outside Circle and Student Facilitator and Explaining (SFAE), Preview-Review models using realia, and guided inquiry models combined with pair cards. Not only that, teacher training using the PPP (Presentation, Practice, and Production) method is also a concern to improve teachers' ability to teach bilingually.Results from various studies show that these models are successful in making students more active, understand the material better, and be more confident in using English. For example, the Inside-Outside Circle and SFAE models encourage students to discuss and exchange information, while the Preview-Review method with real media and the play and sing method make learning more interesting and easy to understand. Meanwhile, the guided inquiry model was found to be highly effective in improving students' engagement and learning outcomes in thematic lessons.Overall, these studies confirm that the use of active and interactive learning methods is essential in bilingual learning to make learning more enjoyable, communicative and effective for primary school students.